The Humanizing Dimension of Prayer in the Time of Covid 19 - Soto Rivas, Víctor Pablo (2020)
In the context of the global pandemic caused by COVID-19, in which man seeks God in prayer to find meaning in his suffering, this article seeks to make known the humanizing dimension of prayer, understood as the presence of God within man that leads him to quench his thirst for God and thus find, through prayer, the strength and peace he needs in the midst of pain and suffering